Clients and their professional advisers’ role in construction materials purchasing functions - Samarasinghe, DAS; Tookey, J; Rotimi, J.O.B.; Windapo, A (Emerald, 2012)
The material purchasing function is the central factor to minimise the overall cost of a building construction project as it contributes to approximately half of the final construction cost. Contractors, subcontractors, clients and consultants are the key personnel involved in the purchasing function in most building construction projects. Clients and their professional advisers could play a significant role in material purchasing functions, but there is evidence to suggest that far too little attention has been paid to their relevance in developing material purchasing strategies. Literature does not provide answers on how the roles of clients can be described in relation to various purchasing activities such as sourcing, selection and procurement of key material inputs; and other routines including feedback and evaluation in relation to price. The paper presents information to show the significance of clients and professional advisers in material management. The paper is an aspect of a wider research that explores how contractors could secure best prices for key materials on construction projects in New Zealand. It describes the methodology for data collection and analyses that will meet the research objectives identified. It is hoped that the result of the research investigations will be beneficial to project participants and the wider construction industry by understanding the complexities involved in procurement decisions and strategies for securing best prices for construction materials.
Keywords: Clients; Construction materials; Purchasing function